Percutaneous Endoscopic Gastrostomy (PEG) Tube Placement in Frail Patients: Exploring Postprocedural Outcomes and Readmissions Using the National Readmission Database, 2018–2020 - Changela, Madhav; Kaneriya, Maulik; Tan, Ernestine Faye; Bahirwani, Janak; Rathod, Vaishnavi Mahendrasinh; Patel, Nishit; Bodrya, Krishna; Hehr, Rohan; Chovatiya, Juhi Ardeshna; Panigrahi, Kalpana; Hasan, Muhammad (Journal of Digestive Endoscopy, 2025)
Percutaneous endoscopic gastrostomy (PEG) tube placement is a common gastrointestinal procedure that provides nutrition, fluids, and medications to patients with inadequate oral intake. A substantial proportion of patients undergoing PEG tube placement are frail. This study compares mortality, morbidity, and 30-day hospital readmission rates between frail and nonfrail patients undergoing PEG tube placement.We conducted a retrospective analysis using data from the National Readmission Database for 2018 to 2020. The study included all patients aged ≥ 18 years who underwent PEG tube placement. Patients were stratified into two groups based on frailty, defined using the Johns Hopkins Adjusted Clinical Groups Frailty Indicator. Primary outcomes were mortality and all-cause 30-day readmission rates. Secondary outcomes included length of stay (LOS), total hospitalization charges, and inpatient complications such as sepsis and aspiration pneumonia.A multivariate regression model was used to estimate clinical outcomes between the two cohorts after adjusting for potential confounders.A total of 419,313 patients underwent PEG tube placement, among whom 278,564 (66.43%) were frail. Frail patients had higher mortality (p = 0.003), longer LOS, and higher all-cause readmission rates than nonfrail patients. Rates of gastric perforation and intraprocedural puncture/laceration were lower in frail patients. The most common causes of 30-day readmission were sepsis (53.14%), pneumonitis due to inhalation of food and vomit (15.55%), gastrostomy malfunction (6.13%), acute kidney failure (3.38%), and pneumonia, unspecified organism (3.97%). Independent predictors of all-cause readmission included frailty, age, Charlson Comorbidity Index, hospital bed size, and insurance, all statistically significant.Frail patients undergoing PEG tube placement have higher mortality, morbidity, and readmission burden. These findings highlight the need for caution when performing PEG tube placement in frail patients. Further research is warranted to validate these findings.
Keywords: percutaneous endoscopic gastrostomy (PEG) tube; frailty; mortality; hospital readmission rate; morbidity; Johns Hopkins Adjusted Clinical Groups (ACG) Frailty Indicator